Central bank digital currencies (CBDCs) in Latin America and the Caribbean - Viviana Alfonso C.; Steven Kamin; Fabrizio Zampolli (Latin American Journal of Central Banking (LAJCB), 2025)
The pros and cons of CBDCs have been examined in numerous writings but much less research has focused on specific economies or regions. This paper attempts to fill that gap for the Latin American and Caribbean (LAC) economies. It first examines the views of central banks in the region toward CBDCs, drawing on a BIS survey conducted in late 2020 and early 2021. It finds that a large share of LAC central banks are engaged in CBDC research, as in other regions, and that their interest is primarily centred around financial inclusion, efficiency, and safety of the domestic payments system. Second, the paper examines whether the engagement of LAC central banks with CBDCs can be explained by the structural characteristics of their economies. It finds higher engagement in countries with strong innovation, fast payment systems, high government effectiveness, high financial development, and strong interest in CBDCs by the public. LAC jurisdictions are generally weaker in these areas than in advanced economies but are broadly comparable to other EMDEs. Third, the paper identifies potential benefits of CBDCs that are particularly relevant for LAC economies: promotion of financial inclusion; reduction of informality; increasing the resilience of the payment system in the face of natural disasters; increasing competition in the payments system; and reducing the cost of cross-border payments. The paper also discusses the costs and risks of CBDCs but argues that these can be addressed through proper design and implementation. Finally, the paper reviews the design choices made by a number of central banks in the region and the associated implementation issues. Common features of CBDCs in use include a two-tier architecture, offline capabilities, restriction to be used only by residents, and safeguards for privacy, but they differ in their approach to ledger management.
Keywords: E42; E51; F31; G21; G28; O32; O38; 330; CBDC; Central bank digital currency; Central banking; Digital currency; Payment systems